Cell polarity: squaring the circle. - Bilder, D. (Current Biology, 2001)
Recent studies have found that Drosophila gene products required for zonula adherens formation in the ectoderm are also involved in the asymmetric cell division of the neuroblast. The results illustrate the reiterated use of groups of proteins to dictate cell polarity in epithelial and non-epithelial cells.